Kewibawaan Guru Pendidikan Agama Islam sebagai Modal Moral dalam Pendidikan Karakter Siswa Sekolah Dasar - Yudha Wijaya Lubis; Auly Dalina; Fawwazatul Ulfa Lubis; Shafwan Adiwangsa Lubis (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to examine the authority of Islamic Education teachers as a form of moral capital in shaping character education among elementary school students. The research employed a qualitative method using a case study approach at SD Negeri 104267 Pegajahan. The primary subjects of the study were Islamic Religious Education (PAI) teachers, while the informants consisted of students, fellow teachers, and the school principal. Data were collected through observations, in-depth interviews, and documentation studies, then analyzed thematically to identify patterns related to teacher authority and character formation. The findings indicate that the authority of Islamic Religious Education teachers functions as a moral force recognized and respected by students, making it an important asset in the internalization of character values. This authority was formed through exemplary behavior, consistency in attitudes, and the establishment of humanistic pedagogical relationships between teachers and students. Through these qualities, teachers became moral role models who positively influenced students’ character development both inside and outside the classroom. The study concludes that strengthening teacher authority as moral capital is an effective strategy for realizing authentic, meaningful, and sustainable character education in elementary schools, as teacher authority should not only be viewed institutionally but also as a moral resource that significantly contributes to students’ personal and social development.